2014
DOI: 10.1038/hdy.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the effects of selection from demographic history in the genetic variation of two sister passerines based on mitochondrial–nuclear comparison

Abstract: Determining the mechanisms responsible for the distribution of genetic diversity in natural populations has occupied a central role in molecular evolution. Our study was motivated by the unprecedented observation that a widespread Eurasian flycatcher, Ficedula albicilla, exhibited no variation at the mitochondrial DNA (mtDNA) ND2 gene in 75 individuals sampled over a 5000-km distance. In contrast, its sister species, F. parva, had low but considerably higher levels of mtDNA variation. We assessed whether natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…By contrast, intra-population genetic diversity can also be strongly influenced by natural selection and changes in population size [11,48,49]. The neutrality tests reveal no evidence of selection on the mtDNA and nuDNA in this study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…By contrast, intra-population genetic diversity can also be strongly influenced by natural selection and changes in population size [11,48,49]. The neutrality tests reveal no evidence of selection on the mtDNA and nuDNA in this study.…”
Section: Discussionmentioning
confidence: 64%
“…However, our goal here is to provide a retrospective analysis on the mtDNA era of phylogeography and estimate the credibility of nearly three decades of mtDNA studies. Many studies have found that the results based on multiple nuclear genes or genome-wide data are often consistent with those based on one single mtDNA gene data in phylogeographic patterns or species delimitation ( [8,11,[44][45][46]56]; but see [5,41,42]). Here, we provide empirical data confirming the assertion that mtDNA is a useful marker for detecting recent population differentiation because of its fast coalescent time at least in avian taxa (figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such protein‐altering replacements at positions that are otherwise conserved over large evolutionary timescales may be slightly deleterious or/and counteracted by compensatory changes in the nuclear‐coded mitochondrial proteins (Osada & Akashi ) or may truly reflect adaptation (Veilleux et al . ; Hung & Zink ).…”
Section: Discussionmentioning
confidence: 99%